The state of the art of dengue in northeast Brazil (Research, Society and Development, 2023)
Introduction: The dengue virus, through the vector mosquito of the genus Aedes spp., causes dengue, which was responsible for about 2.1 million cases in 2019 in Brazil. The Northeast region of Brazil is the second most prevalent in dengue cases, accounting for about ⅕ of the notifications that year. This study aims to understand the state of the art of dengue virus infection in Northeastern Brazil. Methodology: Systematic study of the literature using the keywords “Dengue” and “Brazilian Northeast” in the SciELO, Lilacs and Pubmed/Medline search platforms, which took place during the month of October 2021. Results and Discussion: Virus infection of dengue is correlated with the space-time dynamics of the mosquito and the social determinants of health of social groups, the analysis of previous outbreaks and the current situation of the dengue virus infection, and the predictive models of outbreaks, which allow for adoption of primary and secondary preventive measures against dengue. Conclusion: Dengue in the northeastern states is closely related to the social determinants of health of socioeconomic groups, which can be detailed through the application of predictive models with the adoption of measures to combat the vector mosquito.